2010
DOI: 10.1111/j.1536-7150.2010.00714.x
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Natural Rate of Crime?

Abstract: Studies in the economics of crime literature have reached mixed conclusions on the deterrence hypothesis. One explanation that has been offered for the failure to find evidence of a deterrent effect in the long run is the natural rate of crime. This article applies univariate unit root tests to crime series for the United Kingdom and United States and panel unit roots to crime rates for a panel of G7 countries to examine whether there is a natural rate of crime. Our main finding is that when we allow for two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
(76 reference statements)
2
10
0
Order By: Relevance
“…It can be concluded that all the variables in the system estimated were I(1) 1 except for conviction rate which is found to be integrated of order 0 or I(0). Findings are consistent with Greenberg (2001) and Narayan et. al.…”
Section: Resultssupporting
confidence: 91%
“…It can be concluded that all the variables in the system estimated were I(1) 1 except for conviction rate which is found to be integrated of order 0 or I(0). Findings are consistent with Greenberg (2001) and Narayan et. al.…”
Section: Resultssupporting
confidence: 91%
“…Briefly, it postulates that although crimethwarting policies such as stringent policing and punishment if apprehended can deter criminal activity and reduce crime rates, in the long-run crime will return to its natural level. For instance, Narayan et al (2010) report's results strongly suggest the presence of a natural rate of crime among the G7 group of countries. Thus, it could be argued that if a convergence process in crime rates is established in the case of the sample of European countries used here, it could also be interpreted in terms of the natural crime rate level discourse in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…They labeled this phenomenon as “Criminals’ Learning by Doing.” This may help explain why, over the long run, the level of crime is positively associated with police expenditures. Similarly, Narayan et al (2010) compiled two annualized time series datasets on violent and property crime reported in the United States from 1960 to 2006 and aggregated total crime rates in Great Britain from 1898 to 1999. They sought to determine if there is such as thing as a natural rate of crime.…”
Section: Discussionmentioning
confidence: 99%